Feedlot performance of nine hybrid sorghum grains fed to steers winter, 1971-1972 - McCollough, R.L.; Riley, Jack G.; Drake, C.L.; Roth, G.M. (Kansas State University. Agricultural Experiment Station, 2011)
Previous trials here indicated a possible difference in nutritional values of different hybrid sorghum grains with yellow endosperm hybrids being superior to white endosperm. We compared feedlot performance of yellow endosperm, white endosperm, all waxy (amylopectin type starch), and part waxy hybrid sorghum grains.
Keywords: Beef; Feedlot performance; Hybrid sorghum; Steers